The effect of concurrent connection in the fairness and protection of scheduling mechanism in the internet - Miaji, Yaser; Hassan, Suhaidi (International Association of Computer Science and Information Technology Press (IACSIT), 2012)
Current advance in all type of live technology makes its users greedier in demanding more services with fewer prices.This also, applied for network users who increase their hunger to network resources as the technology increase.The purpose of this paper is to explore and examine the impact of greedy users who initiate simultaneous connections to acquire the same file but from different destination.This method is actually been used by P2P, download accelerator software and others. To approach the aim of verifying the impact of concurrent connection, OPNET simulator is used and the results achieved and accumulated from the simulation is analyzed.The result of the simulation shows side effects of such behavior in the delay variation, end-to-end delay and hence the QoS.This research provides verification and validation for the negative impact of the misbehaved users in network performance, QoS and real-time applications although it has the limitation of implementation in simulation environment with static behavior.However, this study uses reliable topology and the run time is reasonable and justified to proof it’s significant.All findings which accumulated from the simulation is highly contributed to the knowledge of networking particularly in QoS enhancement since this result proof the importance of research in finding new solution to eliminate the miss-behaved effect and motivates scholar redirect their research toward fairer and protective network.